The Impact of Complete Surgical Staging Upon Survival in Early-Stage Ovarian Clear Cell Carcinoma: A Multi-institutional Retrospective Study. Issue 8 (1st November 2009) - Takano, Masashi; Sugiyama, Toru; Yaegashi, Nobuo; Suzuki, Mitsuaki; Tsuda, Hiroshi; Sagae, Satoru; Udagawa, Yasuhiro; Kuzuya, Kazuo; Kigawa, Junzo; Takeuchi, Satoshi; Tsuda, Hitoshi; Moriya, Takuya; et al.
Abstract : Pure-type clear cell carcinoma (CCC) has been recognized as a distinct subtype of ovarian cancer, showing resistance to conventional platinum-based chemotherapy and resulting in poor prognosis. The aim of the study was to evaluate the effects of complete surgical staging procedures for early-stage CCC patients in a retrospective multi-institutional analysis. During the period 1992 to 2002, a total of 199 patients with pT1 M0 CCC were identified. Survival analysis was estimated by Kaplan-Meier methods, and prognostic factors were evaluated using a Cox regression model. Among pT1 M0 tumors, retroperitoneal lymph node status was negative in 125 cases (pN0, 63%), positive in 10 cases (pN1, 5%), and unknown in 64 cases (pNx, 32%). Progression-free survival of pN1 was significantly worse than that of pN0 ( P < 0.05), whereas there was no significant difference between pN1 and pNx. There was no significant difference of overall survival (OS) among the 3 groups. Multivariate analysis revealed that peritoneal cytology status was the only independent prognostic factor for progression-free survival ( P = 0.04), but completion of surgical staging procedures was not a prognostic factor. There was no significant prognostic factor for OS. Our study implied that complete surgical staging enabled us to distinguish a high-risk group of recurrence in pT1 M0 CCC; however, the procedure could not improve OS. Although the study was a limited retrospective study, the impact of peritoneal cytology status was more important than complete surgical staging procedure in CCC patients. More effective treatment modality was warranted, especially for CCC cases positive for malignant peritoneal cytology.